2016
DOI: 10.1200/jco.2015.65.7270
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Evaluating the Impact of Site of Metastasis on Overall Survival in Men With Castration-Resistant Prostate Cancer

Abstract: Listen to the podcast by Dr Agarwal at www.jco.org/podcastsReports have suggested that metastatic site is an important predictor of overall survival (OS) in men with metastatic castration-resistant prostate cancer (mCRPC), but these were based on a limited number of patients. We investigate the impact of site of metastases on OS of a substantial sample of men with mCRPC who received docetaxel chemotherapy in nine phase III trials. Patients and MethodsIndividual patient data from 8,820 men with mCRPC enrolled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
305
4
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(329 citation statements)
references
References 24 publications
11
305
4
9
Order By: Relevance
“…13 In addition, a recent meta-analysis evaluating the impact of site of metastasis on overall survival in men with CRPC showed that liver metastasis predicted worse OS compared to bone metastasis and lymph node only metastasis (13.5 vs 21.3 vs 31.6 months, respectively). 14 In addition to OS, we observed that the 6-factor prognostic index model is predictive of time to PSA progression, PSA response and time on treatment in chemotherapy-naïve patients treated with abiraterone. The use of PSA parameters as a surrogate endpoint for OS in CRPC has generated considerable discussion and controversy.…”
Section: Cuaj -Original Research Khalaf Et Al Stratifying Clinical Oumentioning
confidence: 70%
“…13 In addition, a recent meta-analysis evaluating the impact of site of metastasis on overall survival in men with CRPC showed that liver metastasis predicted worse OS compared to bone metastasis and lymph node only metastasis (13.5 vs 21.3 vs 31.6 months, respectively). 14 In addition to OS, we observed that the 6-factor prognostic index model is predictive of time to PSA progression, PSA response and time on treatment in chemotherapy-naïve patients treated with abiraterone. The use of PSA parameters as a surrogate endpoint for OS in CRPC has generated considerable discussion and controversy.…”
Section: Cuaj -Original Research Khalaf Et Al Stratifying Clinical Oumentioning
confidence: 70%
“…All of these three were sclerotic lesions, SUVmax range was 1.06-1.08 and PSA value was 3.6-240 (Table 2). The skeleton is the second most frequent site (after lymph nodes) for metastases from prostate cancer, and the incidence of skeletal involvement is 65-75% among patients with advanced disease [9] . Among the 15% of patients with bone lesions in this study, were avid on bone scan (23.1%) while the majority (76.9%) were non-avid.…”
Section: Resultsmentioning
confidence: 99%
“…Halabi et al reported a ratio of 1.4 between patients with bone metastases only and those with bone plus lymph node metastases (78).…”
Section: Prognostic Factorsmentioning
confidence: 99%